2014
DOI: 10.1111/apa.12816
|View full text |Cite
|
Sign up to set email alerts
|

Questionable sound exposure outside of the womb: frequency analysis of environmental noise in the neonatal intensive care unit

Abstract: Measuring the frequency spectra of NICU sounds is necessary to attain a thorough understanding of both the noise levels and the type of sounds that preterm infants are exposed to throughout their hospital stay. The risk of high-frequency noise exposure in the preterm population is still unclear and warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 30 publications
1
31
0
1
Order By: Relevance
“…These findings can also be interpreted in the context of the infants' abilities to extract regularities during specific dynamic pattern exposures (here music) creating thus a kind of early perceptual habit as defined by Graybiel (2008). Furthermore, extensive research has shown that noise levels in NICUs are often higher than general recommendations (White et al, 2013;Lahav, 2015) This loud noise has a negative effect on the stability of the cardio-respiratory system, behavior and sleep of the preterm infants (Aly and Ahmed, 2016;Joshi and Tada, 2017) and is presumed to have long lasting effects in preterm infants language and behavioral development (Lahav and Skoe, 2014). Our results support the view that preterm infants can learn from their auditory environment and that preterm infants could have memory also for auditory dis-stimulation and thus warrant for ambient noise reduction in NICU.…”
Section: Discussionmentioning
confidence: 95%
“…These findings can also be interpreted in the context of the infants' abilities to extract regularities during specific dynamic pattern exposures (here music) creating thus a kind of early perceptual habit as defined by Graybiel (2008). Furthermore, extensive research has shown that noise levels in NICUs are often higher than general recommendations (White et al, 2013;Lahav, 2015) This loud noise has a negative effect on the stability of the cardio-respiratory system, behavior and sleep of the preterm infants (Aly and Ahmed, 2016;Joshi and Tada, 2017) and is presumed to have long lasting effects in preterm infants language and behavioral development (Lahav and Skoe, 2014). Our results support the view that preterm infants can learn from their auditory environment and that preterm infants could have memory also for auditory dis-stimulation and thus warrant for ambient noise reduction in NICU.…”
Section: Discussionmentioning
confidence: 95%
“…Because exposure to noise during early development is a highly probable occurrence, particularly for preterm infants exposed to life-support systems (Surenthiran et al, 2003;Lahav, 2014;Laubach et al, 2014;Park et al, 2014), a better understanding of the effects of noise-induced damage on ribbon synapses during early development is important for the formulation of noise safety guidelines. Thus, the present study examined the effects of noise-induced silent damage on ribbon synapses in neonatal mice during the early onset of hearing.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the hospital environment contains a significant amount of high-frequency electronic sounds (52,53) that are less likely to be heard in the womb because of the sound attenuation provided by maternal tissues and fluid within the intrauterine cavity (54)(55)(56). Efforts to improve the hospital environment for preterm neonates have primarily focused on reducing hospital noise and maintaining a quiet environment.…”
mentioning
confidence: 99%